Appraising freedom of information right in Nigeria in the light of international standard (2017)
Freedom of information is now considered a fundamental right of individuals at the international level as it acts as a fulcrum upon which many other rights recline. It is realized that right to freedom of information encourages transparency in government and promotes good democratic culture. This right is now gaining international recognition - though the precise scope of this freedom is not generally ascertainable. The level of making information available to the public by the government or private sector carrying out public responsibilities varied from country to country. Nigeria also acceded to the clamour for the enactment of freedom of information law by the passage of the Freedom of Information Act, 2011 in order to allow the citizens have access to certain government information. This very step has relaxed the age long practice of making government information a top secret and removed from the public glare especially through some enacted legislation like the Evidence Act and the Official Secrets Act, among others. This notwithstanding, it has been observed that the standard of making information available to the public in Nigeria is still at very low ebb. The Freedom of Information Act 2011, though a good step in the right direction, does not totally accommodate the required standards or international best practices and principles of freedom of information laws. Certain lop-sidedness is observed in the provisions of the Act and suggestions are made for reforms.